Lessons learned from 5 years of newborn screening for congenital adrenal hyperplasia in the Czech Republic: 17-hydroxyprogesterone, genotypes, and screening performance - Votava, Felix; Novotna, Dana; Kracmar, Petr; Vinohradska, Hana; Stahlova-Hrabincova, Eva; Vrzalova, Zuzana; Neumann, David; Malikova, Jana; Lebl, Jan; Matern, Dietrich (European journal of pediatrics, 2012)
The aims were to summarize the experience and to determine the performance metrics of newborn screening (NBS) for congenital adrenal hyperplasia (CAH) in the Czech Republic. 17-Hydroxyprogesterone (17OHP) was measured in NBS samples prospectively in 545,026 newborns and retrospectively in 31 CAH patients born outside the study period. A total of 2,811 screened newborns had abnormal 17OHP; CAH was confirmed in 46 probands. One patient with a severe-moderate genotype of CAH had 17OHP below the cut-off and was diagnosed clinically. This corresponds to a screening sensitivity of 98% and a false positive rate (FPR) of 0.51%. The median of 17OHP in the most severe genotypes was 484 nmol/L (n = 21); in severe/moderate, 321 nmol/L (n = 30); in moderate, 61 nmol/L (n = 20); and in mild genotypes, 31 nmol/L (n = 7). NBS is efficient to detect severe CAH but may fail to detect milder variants. However, the FPR is too high but could be improved by application of a second tier test.
Keywords: Genotype; Female; False Positive Reactions; biologické markery; novorozenec; Biomarkers; ženské pohlaví; Neonatal Screening; lidé; steroid-21-hydroxylasa; Infant, Newborn; Sensitivity and Specificity; genotyp; senzitivita a specificita; Humans; 17-alfa-hydroxyprogesteron; retrospektivní studie; falešně pozitivní reakce; prospektivní studie; Male; Prospective Studies; Czech Republic; Česká republika; kongenitální adrenální hyperplazie; genetické markery; mužské pohlaví; novorozenecký screening; Steroid 21-Hydroxylase; Retrospective Studies; 17-alpha-Hydroxyprogesterone; Adrenal Hyperplasia, Congenital; Genetic Markers